Challenges Faced by Agents in Sales Performance on Life Insurance in Karnali, Nepal - Shahi, Dilip Jung (Journal of Economics and Management, 2026)
The insurance penetration in the life insurance sector is still grave in Nepal, especially in the at-risk areas like Karnali Province where distribution has been adversely affected due to limited financial literacy, societal and economic factors and infrastructures. Life insurance agents are very essential as mediators, but their sales are influenced by several factors. This paper discussed issues affecting the performance of the agents and, in this case, the socio-economic aspect, awareness and trust of the customers, and organizational and policy-specific effects. A cross-sectional study of 150 operative agents indicated that the three factors are highly influential on sales performance. Organizational and policy-related factors proved to be the most influential predictor among them, and then went awareness and trust, and socio-economic factors. Regression model could explain 66 percent of the variance in sales performance, which highlights the role of the institutional support of the sales performance and customer engagement. The results reveal that the success of agents does not only depend on personal effort but very closely with organizational structures, training, motivation and favorable policies. Insurance distribution could be significantly improved in underserved areas through the enhancement of these areas, as well as efforts to instill customer confidence and increase financial literacy. The research will be of practical use to the different insurers, policymakers, and researchers that seek the extension of life insurance cover in developing economies such as Karnali Province.